Mathematics : Mechanics and Probability - Bostock, L. and Chandler, S. (Cheltenham Nelson Thornes Ltd., 2002)
This volume deals with Mechanics and the solving of mechanical problems with the help of Pure Mathematics. An appreciation of the properties of vectors is introduced at an early stage, and throughout the book problems are solved using vector methods where appropriate.
Include Index
Keywords: Mathematics -- Mechanics